(3GdQSGdI GdCSjhWjIs - (3eLghds ((3eQJVi Hf YHO GdcQjes)
(3ChdgG (B:s
(3GdMeO ddg (B..(3bhdg JYGdi dc Gddg eG JbOe ef PfHc heG JCNQ , gPg GdBjI ajgG CbhGd ddeaSQjf HYVgG ebHhd hHYVgG eQOhO hHYVgG VYja ddOdjd GdbGWY Ydi YUeI GdfHj Udi Gddg Ydjg hSde (B...s
(3BNQgG (B:s
... (3hdYd GddaX eSHM HGdSjf haJM Gdeje jYfj YQjV ceG hbY aj GdQhGjI GdCNQi hMcGg GHf OQjO hGdcQGOHSj QDhS GdYXGe hgh eKd bhdg GdMOjK GdBNQ (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds